2021
DOI: 10.1101/2021.06.01.446505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optogenetic stimulation of primate V1 reveals local laminar and large-scale cortical networks related to perceptual phosphenes

Abstract: Developing optogenetics in non-human primates (NHPs) is essential for translating its successful implementation in rodents to clinical applications in humans. However, information about how optogenetics influences the primate cortex remains limited. Here, we evaluate how optogenetic stimulation of the primate primary visual cortex (V1) affects local and large-scale network activation concerned with visual perception. To this end we injected an optogenetic construct (AAV9-hSyn-ChR2-eYFP) into the V1 cortex of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
7
0
1
Order By: Relevance
“…2012 ; Ohayon et al. 2013 ; Ortiz-Rios et al. 2021 ), a challenging but promising method for investigating effective connectivity in vivo.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2012 ; Ohayon et al. 2013 ; Ortiz-Rios et al. 2021 ), a challenging but promising method for investigating effective connectivity in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies showed that optogenetic stimulation of the primary visual cortex (V1) evoked activities only in V1 and the areas directly connected to V1 ( Nakamichi et al. 2019 ; Ortiz-Rios et al. 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expression of a microbial opsin in the visual cortex was found to activate cortical neurons even in the cortex depth following surface illumination of the brain. 55 57 In non-human primates, this cortical activation produced visual saccades toward the corresponding point in the visual field 55 , 56 , 58 and was able to elicit activity in other visual areas as indicated by functional magnetic resonance imaging (fMRI). 58 More subtle changes were described, such as an increased sensitivity to the stimulus orientation, only when the optogenetic stimulation was applied on a column with an orientation selectivity close to that of the stimulus.…”
Section: Introductionmentioning
confidence: 99%
“… 55 57 In non-human primates, this cortical activation produced visual saccades toward the corresponding point in the visual field 55 , 56 , 58 and was able to elicit activity in other visual areas as indicated by functional magnetic resonance imaging (fMRI). 58 More subtle changes were described, such as an increased sensitivity to the stimulus orientation, only when the optogenetic stimulation was applied on a column with an orientation selectivity close to that of the stimulus. 59 , 60 Furthermore, optogenetic activation of single ocular dominance columns generated preferential activation of nearby same-eye columns.…”
Section: Introductionmentioning
confidence: 99%